Testing of the Structure and Mechanical Properties of Technical Titanium Joints - Bogumił Wronka (Advances in Materials Science and Engineering)
The aim of the research was the titanium pipeline welding technology. The transformations of this material due to the influence of thermal welding were analysed. The basic purpose was to evaluate the properties of titanium joint areas. Pipe joints of various thicknesses were welded by means of TIG argon arc welding while applying the optimum and reduced gas flow intensities. The structure and mechanical properties of these joints were tested. Different test results were obtained for joints welded in these two conditions. Recommendations concerning the welding technology and the heat treatment of joints after welding were presented.